2023
DOI: 10.3389/fpls.2022.1050359
|View full text |Cite
|
Sign up to set email alerts
|

Selenium seed priming enhanced the growth of salt-stressed Brassica rapa L. through improving plant nutrition and the antioxidant system

Abstract: Various abiotic stresses may affect the germination, growth, and yield of direct-seeded vegetable crops. Seed priming with effective antioxidant mediators may alleviate these environmental stresses by maintaining uniformity in seed germination and improving the subsequent health of developing seedlings. Salt-induced stress has become a limiting factor for the successful cultivation of Brassica rapa L., especially in Southeast Asian countries. The present study was performed to elucidate the efficacy of seed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…The proline synthesized through the glutamate pathway helps maintain the redox balance of plants under salt stress [42]. The introduction of exogenous Se alleviated the osmotic stress caused by high salt in the roots of plants and reduced the proline content in plants (Figure 5A), which is consistent with the study result of Hussain and Yao et al [43,44].…”
Section: Discussionsupporting
confidence: 89%
“…The proline synthesized through the glutamate pathway helps maintain the redox balance of plants under salt stress [42]. The introduction of exogenous Se alleviated the osmotic stress caused by high salt in the roots of plants and reduced the proline content in plants (Figure 5A), which is consistent with the study result of Hussain and Yao et al [43,44].…”
Section: Discussionsupporting
confidence: 89%
“…Soil salinization is a major environmental stressor hindering global crop production, risking food security and weakening global efforts towards the Sustainable Development Goals ( Wang et al., 2022 ). Because saline soil affects seed germination and seedling establishment ( Farooq et al., 2015 ), priming crop seeds before germination has emerged as a promising approach to reduce seedling salt stress and enhance crop yields on salinized land ( Hussain et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Higher MDA and H 2 O 2 levels in the floral buds of a non-heading Chinese cabbage line were observed, indicating a positive correlation between these two compounds (Yuan et al 2007). Prior studies found a positive correlation between POD and (MDA) accumulation in Brassica, with an increase in MDA under salinity stress (Hussain et al 2024). This suggests that peroxidase activity may be linked to MDA production in response to stress.…”
Section: Discussionmentioning
confidence: 80%